Early responses of primary human and bovine monocytes, monocytic THP-1 cells and THP-1 cell-derived macrophages to vital Toxoplasma gondii tachyzoites - Hanke, Dominik; Velásquez, Zahady D.; Büttner, Kathrin; Krueger, Andreas; Ross, Ralf; Hecker, Andreas; Mazurek, Sybille; Grau, Veronika; Taubert, Anja; Hermosilla, Carlos; Richter, Katrin; Conejeros, Iván (Frontiers in Immunology, 2025)
IntroductionDifferent innate immune cell types are known to release extracellular traps (ETs) in response to invasive pathogens, including parasites. These ETs function to trap, immobilize, and eventually kill pathogens. In line with this, monocytes and macrophages have been shown to release ETs, known as monocyte/macrophage extracellular traps (METs). Toxoplasma gondii (T. gondii) is an apicomplexan zoonotic parasite that infects humans and homeothermic animals. While most studies have focused on prolonged exposure of immune cells to T. gondii, this study characterized the early innate immune reaction of mononuclear phagocytes to vital T. gondii tachyzoites.MethodsPrimary human and bovine monocytes, monocytic THP-1 cells, and THP-1 cell-derived macrophages (M0-, M1-, and M2-like) were exposed to T. gondii tachyzoites for 4 h. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), immunofluorescencemicroscopy, and confocal microscopy were used to visualize cell activation and the presence of METs. Additionally, the release of pro-inflammatory cytokines interleukin (IL)-1β and IL-6, and expression of Toll-like receptor (TLR) 2 and TLR4 were analyzed.Results and discussionMicroscopic analysis illustrated the activation of all cell types tested within 4 h of exposure to T. gondii tachyzoites. Numerous tachyzoites were found intracellularly in THP-1 cell-derived M1-like macrophages. Furthermore, the co-localization of extracellular DNA (extDNA) and histones in extracellular web-like fibers proved classical characteristics of extruded T. gondii-induced METs, although this was a rare event. In primary human monocytes, an increased release of IL-1β and IL-6 was observed following exposure to T. gondii tachyzoites. When co-stimulated with lipopolysaccharide (LPS), primary human monocytes showed an enhanced release of IL-1β and IL-6 in response to T. gondii. In contrast to monocytic THP-1 cells, THP-1 cell-derived M1-like macrophages released IL-1β in response to T. gondii tachyzoite exposure. When additionally stimulated by LPS, all THP-1 cell-derived macrophages showed an enhanced release of IL-1β, and monocytic THP-1 cells an increased release of IL-6 in response to T. gondii tachyzoites. This study provides insights into the early innate immune response of human and bovine mononuclear phagocytes to T. gondii. While cytokine secretion was prominent, MET formation was rare in the early response (i.e. < 4 h of exposure) to T. gondii tachyzoites.